2015
DOI: 10.1037/ort0000077
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medical services and “psych calls”: Examining the work of urban EMS providers.

Abstract: Emergency medical technicians and paramedics form the backbone of the United States' Emergency Medical Service (EMS) system. Despite the frequent involvement of EMS with people with mental health and substance abuse problems, the nature and content of this work, as well as how EMS providers think about this work, have not been fully explored. Using data obtained through observations and interviews with providers at an urban American EMS agency, this paper provides an analysis of the ways in which EMS providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 22 publications
4
66
0
Order By: Relevance
“…Overall, our findings reiterate broader calls for improving the quality of ambulance care for people presenting with mental health and/or AOD issues . A range of measures could be included to achieve this, including an educational approach to address potential skills gaps around communication.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Overall, our findings reiterate broader calls for improving the quality of ambulance care for people presenting with mental health and/or AOD issues . A range of measures could be included to achieve this, including an educational approach to address potential skills gaps around communication.…”
Section: Discussionsupporting
confidence: 63%
“…Australian studies have shown that between 10% and 20% of ambulance presentations are related to mental health and/or AOD concerns . Similar to stigmatizing attitudes documented in the general population and amongst some health professional groups, research indicates that some paramedics display negative attitudes towards people who present with mental health and/or AOD problems . Such negative attitudes may act as a barrier to help‐seeking and recovery in this population …”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…A qualitative study (observations and interviews) by Prener and Lincoln [2] in the US found that urban paramedics and emergency medical technicians were frustrated by what they perceived as “filling the gaps for other health care and social services” in attending to patients with mental health and/or AOD problems. Similarly, studies have documented a perception amongst paramedics that non-medical emergency-related mental health and/or AOD presentations divert resources and attention away from the ‘real’ medical emergency work that paramedics believe should be the primary focus of their work [2, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while an overview of the sociology of work is outside the scope of this article (see, e.g., Abbott ; Gorman and Sandefur ), a major theme within this literature is on the “nature of the work process” (Tope et al :476). The work of paramedics discussed above, and the analysis undertaken below, contribute to the sociological study of work and occupations by first and foremost shedding light on an ever‐important occupational group in health care that has garnered little sociological attention until recently (see, e.g., Prener and Lincoln ; Seim ). In addition, my explicit focus on the hidden and taken‐for‐granted work of paramedics aligns with new directions in research on work and occupations that call for a shift in focus “away from the individual to the conditions and relations of work” (Armstrong 2013:101).…”
Section: Investigations Into the Work Of Paramedics—past And Presentmentioning
confidence: 99%